2020
DOI: 10.1016/j.scitotenv.2020.140112
|View full text |Cite
|
Sign up to set email alerts
|

Association of COVID-19 pandemic with meteorological parameters over Singapore

Abstract: COVID-19 is an emerging infectious disease and highly contagious in nature.• Temperature, dew point, and absolute humidity showed positive significant associations with SARS-CoV-2 transmission. • SARS-CoV-2 displayed negative associations with wind speed and ventilation coefficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
255
1
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(302 citation statements)
references
References 123 publications
34
255
1
12
Order By: Relevance
“…The proposed methodology tends to reproduce Pani et al (2020) methodology to data obtained from the Lombardy region in Italy. However, differently, we add air pollution variables and take consideration on the latency period in response to those variables.…”
Section: Data and Methodsologymentioning
confidence: 99%
See 3 more Smart Citations
“…The proposed methodology tends to reproduce Pani et al (2020) methodology to data obtained from the Lombardy region in Italy. However, differently, we add air pollution variables and take consideration on the latency period in response to those variables.…”
Section: Data and Methodsologymentioning
confidence: 99%
“…With respect to the meteorological conditions, we considered the daily records of the most common meteorological parameters following the approach of Pani et al (2020). The considered parameters with relative explanation are reported in Table 1.…”
Section: Data and Estimationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a study from Singapore revealed that temperature and dew point have a positive impact on the number of daily as well as the cumulative COVID-19 cases (Pani et al, 2020). In another study, Şahin (2020) analysed the impact of weather parameter on COVID-19 in Turkey.…”
Section: Introductionmentioning
confidence: 99%